Harnessing the surface chemistry of methyl ester functionalized polydicyclopentadiene and exploring surface bioactivity. Issue 6 (5th August 2020) - Li, Tong; Shumka, Hannah; Cuthbert, Tyler J.; Liu, Chang; Wulff, Jeremy E.
Abstract : The ester group on a functionalized form of polydicyclopentadiene ( f PDCPD) was harnessed to attach several biologically relevant appendages, including a fluorescent dye, an RGD peptide, and a releasable antibacterial agent to control E. coli growth. Abstract : In an effort to broaden the utility of the industrially used ROMP polymer polydicyclopentadiene, we introduced an ester-functionalized dicyclopentadiene monomer that can be polymerized and crosslinked under similar conditions to those of the unfunctionalized parent, and for which the resulting functionalized polymer ( f PDCPD) maintains the thermal and mechanical properties that make polydicyclopentadiene useful. In the current work, we expand on the utility of f PDCPD by harnessing the embedded functional group to manipulate the surface energy of the material, and to attach a range of biologically relevant functional groups. These include a fluorescent dye used to characterize surface coverage, an RGD peptide used to promote cellular adhesion, and an antibacterial agent (chloramphenicol) used to moderate E. coli growth. Significantly, the chloramphenicol is conjugated to the surface in such a way that it remains inactive until it is cleaved by endogenous bacterial enzymes. This strategy minimizes leaching of the drug into the environment, by effectively relying on colonizing bacteria to dose themselves with surface-available antibiotic.